Income Analysis of the Welfare Level of Red Onion (Allium cepa L) Farmers; Case Study: Shallot Farmers in Topo Village, Tidore District, Tidore City, Islands, North Maluku Province - Aliismet, Ferdasari; Azizah HS, Nur; Radjaloa, Vhyda Hamidah Aulia (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
This study aims to analyze income, the level of welfare of the households of Topo local shallot farmers in Topo Village, Tidore District, Tidore Islands City, Maluku Province. This type of research is quantitative research. The research was carried out for approximately 2 months, from November to December 2022. The analytical method used in this research is quantitative and descriptive qualitative analysis. the research results show that: (1) The total income of the 28 respondent farmers is IDR 178,913,250. where as many as 21 people with an income of 1-10 million and as many as 7 people with an income of 11-20 million. With an average income per harvest of IDR 6,389,759. (2) The level of household welfare of shallot farmers in Topo Village, Tidore District, Tidore Islands City, North Maluku Province is mostly prosperous with a total percentage of 93%.